Penerapan Sistem Pendukung Keputusan Pemilihan Guru Terbaik Menggunakan Metode Analytical Hierarchy Process - Ainun Zumarniansyah (LPPM STMIK ANTAR BANGSA, 2023)
In determining the best teacher, there are several factors into the assessment. This assessment is based on teacher performance assessments at the Prosperous Vocational High School and internal activities. For the sake of efficiency and effectiveness of work, the right decision making is needed. With the aim to build and provide alternatives. decision support system is a system that has the ability to analyze alternatives for selecting the best teachers using the Analytical Hierarchy Process method, where there are several criteria used, namely Achievement, Quality, Discipline, Responsibility, Years of Service for the selection of teachers who each have a weight assessment so as to provide teacher assessment results which provide an assessment of each of the best teacher performance. This decision support system helps and provides alternatives in assessing each teacher. The final result is obtained from the calculation process, namely the sum of the normalized matrices with weights per criterion which shows the ranking of the best teacher selection from the first to the last of the criteria. From this assessment, it becomes an alternative which then gets the best teacher.